Modular synthesis of triaroyl cyclopropanes via a formal cyclotrimerization of phenacyl bromides and their transformation into diazabicycles - Jadhav, Hrutik Madhavrao; Penta, Santhosh; Pannuri, Lavanya Lahari; Rangarao, Chilukuri; Gonnade, Rajesh G.; Manda, Rajesh (Organic Letters, 2026)
Step-efficient cyclotrimerization reactions are entrancing approaches for saturated carbocycles. In this context, we demonstrate the alpha-bromocarbonyl (1+1+1) cyclotrimerization modularity to obtain stereoselective trisubstituted cyclopropanes under metal-free conditions. These cyclopropanes were condensed with hydrazine to afford diazabicyclic adducts and further expanded through a ring expansion reaction. In contrast to the classical alkylating reactivity, alpha-bromocarbonyl cyclotrimerization was also achieved by using various nucleophiles. A wide range of bromoacyl substrates established the broad scope of the transformation.